Application of Mivacurium in Fast-Track Anesthesia for Transthoracic Device Closure of Ventricular Septal Defects in Children - Wang,Jing (2022)
Abstract Introduction: The objective of this study was to investigate the effect of mivacurium in the application of fast-track anesthesia for transthoracic device closure of ventricular septal defects (VSDs) in children. Methods: The data of 108 children who underwent transthoracic device closure of VSDs from December 2018 to June 2020 were recorded and analyzed. All children were divided into group M (mivacurium group, n=55) and group C (cisatracurium group, n=53) according to the different muscle relaxant drug used. Results: No statistically significant differences in general preoperative data, intraoperative hemodynamic changes, or the incidence of adverse reactions were noted between the two groups (P>0.05). However, the intubation condition rating of children in group M was better than that in group C. The onset time, duration of clinical action and recovery index of the muscle relaxant, postoperative mechanical ventilation duration, and length of intensive care unit stay in group M were significantly lower than those in group C (P<0.05). Conclusion: It is safe and feasible to use mivacurium as a muscle relaxant in children undergoing fast-track cardiac anesthesia during transthoracic device closure of VSDs.